Football Medicine - The pursuit of excellence. Book of abstracts (Calzetti & Mariucci Editori, 2023)
The Isokinetic Medical Group, in partnership with FIFA Medical, is proud to present the 30th edition of the Isokinetic Conference. A landmark edition after three decades of our annual gathering, which has always aimed to foster discussion and innovative vision in the different domains of Football Medicine, often across various aspects of performance, with the final goal of perfecting player and patient care. It is indeed a very special edition of our conference. A signature of a generation of the world`s Football Medicine leaders, looking to the next one`s contributions to development in our field.